Social competitiveness associated with rapid fluctuations in sperm quality in male fowl. - Pizzari, T; Cornwallis, C; Froman, D (2007)
When females copulate with multiple males, paternity is determined by the competitive ability of a male to access females and by the ability of its ejaculates to out-compete those of other males over fertilization. The relationship between the social competitiveness of a male and the fertilizing quality of its sperm has therefore crucial implications for the evolution of male reproductive strategies in response to sexual selection. Here, we present a longitudinal experimental study of the relationship between social status and sperm quality. We monitored sperm quality in socially naive male domestic fowl, Gallus gallus domesticus, before and after exposure to a social challenge which comprised two stages. In the first stage, social dominance was established in male pairs divergent in sperm quality, and in the second, social status was experimentally manipulated by re-shuffling males across pairs. We show that sperm quality fluctuates within males both before and after a social challenge. Importantly, such fluctuations followed consistently different patterns in males that displayed different levels of social competitiveness in the social challenge. In particular, following the social challenge, sperm quality dropped in males that won both contests while the sperm quality of males that lost both contests remained constant. Together, these results indicate that males of different social competitiveness are predisposed to specific patterns of fluctuations in sperm quality. These rapid within-male fluctuations may help explain the recent findings of trade-offs between male social and gametic competitive abilities and may help maintain phenotypic variability in these traits.